Persuasion in International Journals: Pragmatic Analysis - Aditama, Madya Giri (2016)
Persuasive in written texts especially in international journals is very interesting to be analyzed. The objectives of the research are to classify the persuasive strategies and to describe hedging strategies applied in persuasive sentences used by native and non-native English author in international journals. The type of the research is descriptive qualitative. The data collecting method used in this research is documentation method by using content analysis techniques. The data sources are international journals, which consist of 25 journals written by native English author and 25 journals written by non-native English author which are chosen randomly and analyzed by using Aristotle's persuasive strategies theory and Hyland's hedges strategies theory. The research findings shows that native authors use 481 persuasive strategies (100%) which consist of 186 Ethos (37,63%), 132 Pathos (27,44%), and 168 Logos (34,93%) application. And in non-native authors found 397 persuasive strategies (100%) which consist of 157 Ethos (39,55%), 32 Pathos (8,06%), and 208 Logos (52, 39%) application. While in the use of hedges strategies, the native authors use 803 hedges (100%), which consist of 62 Attribute Hedges (7,72%), 463 Reliability Hedges (57,66%), 149 Writer Oriented hedges (18,56%), and 129 Reader Oriented Hedges (16,06%). On the other hand, non-native authors used 702 hedges (100%), which consist of 46 Attribute Hedges (6,54%), 411 Reliability Hedges (58,46%), 113 Writer-Oriented hedges (16,07%), and 133 Reader Oriented Hedges (18,92%). This study also discovers some similarities and differences of persuasive and hedging strategies used by native and non-native English authors in writing international journals.